SPEECH COMMUNICATION - Khakimova Nasiba Turgunovna (American Journals, 2023)
the modern educational paradigm defines learning as a controlled educational and cognitive activity, which leads not only and not so much to an increase in the baggage of knowledge, skills and abilities, but to more important changes in the student's personality: an increase in intelligence, the formation of a cognizing personality, psychologically ready for self-realization. At present, the problem of The formation of tolerant consciousness and communicative competence as stable characteristics of the personality of a growing person is especially urgent. The solution of this issue is becoming a real priority of pedagogical science and practice today. The quality of mastering educational material, first of all, depends on the choice of a modern method of studying a particular topic. Linguistic communication should be defined as a process, the essence of which is the transmission of information using language. Since the transfer of information presupposes the presence of the sender and the addressee using a mutually understandable language, linguistic communication is one of the forms of interaction established between people. The author of the article discusses the issue of lingual communication, its theoretical aspects - definition, components and features. In addition, the problem of information transmission is considered and a revised version of the stages of language communication is proposed.
Keywords: Speech activity, verbal information, language communication, linguistic units, communicant, communication, pragmatic and cognitive aspects, speech communication.